The state of the American mind - Bauerlein, Mark; Bellow, Adam (Templeton Press, 2015)
In 1987, Allan Bloom's The Closing of the American Mind was published; a wildly popular book that drew attention to the shift in American culture away from the tenants that made America-and Americans-unique. Bloom focused on a breakdown in the American curriculum, but many sensed that the issue affected more than education. The very essence of what it meant to be an American was disappearing. That was over twenty years ago. Since then, the United States has experienced unprecedented wealth, more youth enrolling in higher education than ever before, and technology advancements far beyond what m.